PENINGKATAN HASIL BELAJAR IPAS PADA MATERI SISTEM PERNAPASAN MANUSIA MELALUI MEDIA PEMBELAJARAN ASPERA DI KELAS V SDN SUNYARAGI 1 - Siska Andriyani; Ikariya Sugesti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the improvement of students' learning outcomes on the topic of the human respiratory system through the use of the ASPERA learning media (Teaching Aids for the Human Respiratory System). The method used is Classroom Action Research (CAR) following the spiral model of C. Kemmis and McTaggart, conducted in two cycles. The research subjects were 27 fifth-grade students of SDN Sunyaragi 1. The data collection technique employed was testing, with test items as the research instrument. Data analysis was carried out both qualitatively and quantitatively using descriptive statistics based on the average scores and mastery learning of the IPAS (Science) subject on the human respiratory system topic. The results showed that in the pre-cycle, the average student score was 64.81, categorized as fair, with a learning mastery percentage of 56%. In Cycle I, the average score increased to 75.19, categorized as good, with a mastery percentage of 74%. Since Cycle I did not meet the success indicator of 85%, the researcher conducted reflection and improvement in Cycle II. In Cycle II, the average student score reached 84.07, categorized as very good, with a mastery percentage of 100%. Thus, the use of the ASPERA learning media (Teaching Aids for the Human Respiratory System) is effective in improving students' learning outcomes on the topic of the human respiratory system in Grade V.